INTEGRATION OF SCHOOL AND PESANTREN EDUCATIONAL SYSTEM AS A MODEL OF CHARACTER EDUCATION: PERSPECTIVE OF EDUCATIONAL TRANSFORMATION - Maksudin sudin (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2018)
Abstract: Educational institutions in Indonesia experience a transformation, institutional forms, education system, and its operation. Transformation also occurs in Islamic educational institutions with various changes and modernization (i) Suffah, Dar al-Arqǎm, Kuttab (in the period of the Prophet and his companions), (ii) madrasah (in the period of tabiin such as Madrasah Nizamiyah), (iii) school (heritage of colonialist), (iv) pesantren (Java), dayah or rangkang (Aceh), and surau (Minangkabau) which are original educational institutions of the native (indigenous),and (v) integrated Islamic schools (SIT) under the network of integrated Islamic schools environment (JSIT), centered in Jakarta. Integration of school and pesantren educational system in 2014 bore SMA TRENSAINS Tebuireng Jombang. The concept of integration is in form of modernization of educational system between schools and pesantren into one system of education. Integration in boarding school system and full day school involves components of the system in form of inputs, process, direct output and indirect output (outcome). This integration is as one of the efforts to make a balance between intellectual, emotional, spiritual and religious intelligence. Those four intelligences are as the basis of character education model.